Effectiveness of the Discussion Method in Enhancing Collaborative Skills in Fourth-Grade Indonesian Language Learning - India Yani, Karmila; Hakim, Lukman; Faipri Selegi, Susanti (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
This study examines the efficacy of the discussion approach in improving collaborative abilities among fourth-grade students in Indonesian Language education at SD Negeri 87 Palembang. The research utilized a quantitative methodology with a quasi-experimental design, specifically the Non-equivalent Control Group Design, involving all fourth-grade students. Class IVA served as the experimental group, while class IVB functioned as the control group, comprising a total of 58 participants selected via saturated sampling. Data were gathered via observation, assessments, surveys, and recordkeeping. The results indicate a notable enhancement in collaboration skills among students subjected to the discussion approach. The experimental class exhibited a rise in mean test scores from 58.03 (pretest) to 82.85 (post-test), whereas the control class demonstrated a lesser gain from 47.33 to 72.33. In the experimental class, questionnaire scores went from 55.07 to 79.17, whereas the control class had an increase from 53.93 to 67.80. The independent sample t-test revealed a significance value of 0.000 (p < 0.05), demonstrating a substantial difference between the two groups and affirming the efficacy of the discussion approach. The findings indicate that the discussion technique enhances students' collaboration abilities while fostering greater engagement and interest in studying the Indonesian Language at the primary school level.